2008
DOI: 10.1002/wnan.3
|View full text |Cite
|
Sign up to set email alerts
|

Radioactive liposomes

Abstract: Many methods of labeling liposomes with both diagnostic and therapeutic radionuclides have been developed since the initial discovery of liposomes 40 years ago. Diagnostic radiolabels can be used to track nanometer-sized liposomes in the body in a quantitative fashion. This article reviews the basic methods of single photon emission computed tomography (SPECT) and positron emission tomography (PET) imaging and labeling of liposomes with single photon and dual photon positron emission radionuclides. Examples of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
82
0
1

Year Published

2010
2010
2014
2014

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 94 publications
(84 citation statements)
references
References 68 publications
1
82
0
1
Order By: Relevance
“…The best-fit parameters (see Fig. 2 (lines) and ESIw) are in the range to be expected based on values obtained for the previously studied low-molecular weight calix [4]arene system. 10 Attempts to prepare liposomes with about equal amounts of chelate on the inner and outer membrane layer with the use of the ''classical'' preparation protocol 6,12 failed; cryo-TEM images showed that complex mixtures of aggregates with a high content of disk-like micelles (bicelles) along with vesicles that were not completely closed or multilamellar (see ESIw) were always obtained.…”
supporting
confidence: 71%
See 4 more Smart Citations
“…The best-fit parameters (see Fig. 2 (lines) and ESIw) are in the range to be expected based on values obtained for the previously studied low-molecular weight calix [4]arene system. 10 Attempts to prepare liposomes with about equal amounts of chelate on the inner and outer membrane layer with the use of the ''classical'' preparation protocol 6,12 failed; cryo-TEM images showed that complex mixtures of aggregates with a high content of disk-like micelles (bicelles) along with vesicles that were not completely closed or multilamellar (see ESIw) were always obtained.…”
supporting
confidence: 71%
“…PET and SPECT) in their cavities. 4 A disadvantage of liposome systems with MRI CAs incorporated in the membrane is that in the systems reported to date, half of the Gd-chelate molecules are oriented inside. These Gd-chelates have poor relaxivities caused by the low water permeability (P w ) of the hydrophobic membranes.…”
mentioning
confidence: 99%
See 3 more Smart Citations